Physicochemical characterization of starches from dry beans cultivated in Brazil. (December 2016) - Demiate, Ivo Mottin; Figueroa, Amanda Miléo; Zortéa Guidolin, Manoela Estefânea Boff; Rodrigues dos Santos, Thais Paes; Yangcheng, Hanyu; Chang, Fengdan; Jane, Jay-lin
Abstract: The objective of this study was to understand physicochemical characteristics and in vitro digestibility of starch from eleven common types of beans grown in Brazil. The bean starch granules showed oval or kidney shapes with indentations, median diameters (D50) from 22.2 to 33.5 μm and had amylose contents from 27.0 to 35.9%. The molecular weight and gyration radius of amylopectin ranged 6.5 × 10 8 –10.5 × 10 8 g/mol and 297–345 nm, respectively. Amylopectin percentage of long chains (DP ≥ 37) and average branch chain length ranged 10.31–13.85% and DP 19.60–21.25, respectively. Gelatinization onset temperatures and enthalpy changes of the starches ranged 54.3–65.9 °C and 12.4–15.9 J/g, respectively. Pasting properties of the bean starches showed peak and final viscosities ranging from 528 to 2860 cP and 811 to 3619 cP, respectively. In vitro digestibility of cooked starch determined using Englyst method showed that rapidly digestible, slowly digestible and resistant starch ranged 89.8–96.7, 2.0–7.4 and 0.0–7.2%, respectively. White kidney bean ( Branco ) displayed the largest content of resistant starch. Graphical abstract: Highlights: Structural analysis and in vitro digestibility of bean starches were studied. Amylopectin branch chain-length distribution was correlated with in vitro digestibility. Cooked bean starches showed high resistant-starch contents for some beans.